PENGARUH PEMBERIAN BERBAGAI JENIS ADENDA DALAM MEDIA ½ MS TERHADAP PERTUMBUHAN SEEDLING ANGGREK PHALAENOPSIS IN VITRO - M, Zasari; Yusnita, Yusnita; O, Saputri (Program Studi Magister Ilmu Pertanian, Fakultas Pertanian, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2015)
Growth of in vitro seedling Phalaenopsis orchid can be enhanced by using ½ Murashige and Skoog (MS) medium which was supplemented with organic additive. The purpose of this study is to investigate the effects of organic additives in the ½ MS medium and to determine the best organic of organic additives on Phalaenopsis seedling growth. Culture medium (½ MS) was supplemented with coconut water, banana pulp, carrot extract, tomato extract and pineapple extract. The results showed that ½ MS medium supplemented with coconut water 100 ml/L could increase growth of Phalaenopsis orchid to the number of roots and wet weight. In addition, ½ MS medium supplemented with 200 g/L showed statistically significant to the leaf length. Furthermore, coconut water is the best organic additive for development of in vitro seedling Phalaenopsis orchid.